Audit Committee and Ethical Accounting: A Study of Listed Consumer Good Firms in Nigeria - Shafi’i Bello, Ibrahim; Abubakar, Abubakar; Usman Hassan, Shehu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This study examines whether Audit Committee physiognomies prevent manager’s discretionary attitudes in listed Nigerian consumer good firms. It covers the period of seven years from 2012 to 2018. Data for the study were extracted from the firms’ annual reports and accounts. The Population of study consists of all 21 listed consumer good firms in Nigeria and eight companies form the sample size. Ordinary least square regression was employed to run the data of the study and robustness test was conducted for validity of statistical inferences. The results from the analysis revealed that audit committee financial expertise and size of the committee showed negative significant with earnings management, while audit committee meetings and earnings management showed significance positive association between audit committee and earning management of the listed consumer good firms in Nigeria. In line with the findings, the study recommended, among others, that listed consumer good firms in Nigeria should strictly comply with the provision of Companies and Allied Matters Act (CAMA) and SEC Code of Corporate Governance on the issues regarding Audit Committees. Also, regulators such as SEC should increase the minimum number of Audit Committee members with financial expertise and also have a statutory position on the maximum number of Audit Committees meetings, which should not be greater than four meetings in a year to improve the ability of the committee to checkmate unethical accounting by managers.